2015
DOI: 10.1016/j.neuron.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

N17 Modifies Mutant Huntingtin Nuclear Pathogenesis and Severity of Disease in HD BAC Transgenic Mice

Abstract: SUMMARYThe nucleus is a critical subcellular compartment for the pathogenesis of polyglutamine disorders, including Huntington’s disease (HD). Recent studies suggest the first 17-amino-acid domain (N17) of mutant Huntingtin (mHTT) mediates its nuclear exclusion in cultured cells. Here, we test whether N17 could be a molecular determinant of nuclear mHTT pathogenesis in vivo. BAC transgenic mice expressing mHTT lacking the N17 domain (BACHD-ΔN17) show dramatically accelerated mHTT pathology exclusively in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 65 publications
4
96
3
Order By: Relevance
“…Recent in vivo studies from Yang and coworkers showed that a ∆N17 variant of huntingtin, which lacks the N17 module, leads to faithful reproduction of HD phenotypes in transgenic mice (56,57). In light of these observations, and given the relative ease of synthesis and purification of Htt-NTFs that lack the N17 module (19), we used constructs of the form Q n -C38 for a majority of our in vitro experiments.…”
Section: Constructs For In Vitro Experimentsmentioning
confidence: 99%
“…Recent in vivo studies from Yang and coworkers showed that a ∆N17 variant of huntingtin, which lacks the N17 module, leads to faithful reproduction of HD phenotypes in transgenic mice (56,57). In light of these observations, and given the relative ease of synthesis and purification of Htt-NTFs that lack the N17 module (19), we used constructs of the form Q n -C38 for a majority of our in vitro experiments.…”
Section: Constructs For In Vitro Experimentsmentioning
confidence: 99%
“…Far less in vivo data with endogenous Htt expression levels, and with deletion mutations generated in the context of the full-length Htt protein exists. However, BACHD-ΔN17 mice, where the N17 domain has been deleted from the expanded Htt allele, have been generated and characterized [124]. In these mice, deletion of the N17 domain results in accelerated and worsened behavioral and neuropathological phenotypes compared to control BACHD mice, demonstrating that the presence of the N17 domain reduces the toxicity of mHtt [124].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%
“…However, BACHD-ΔN17 mice, where the N17 domain has been deleted from the expanded Htt allele, have been generated and characterized [124]. In these mice, deletion of the N17 domain results in accelerated and worsened behavioral and neuropathological phenotypes compared to control BACHD mice, demonstrating that the presence of the N17 domain reduces the toxicity of mHtt [124]. Ultimately, in vivo methods are needed to confirm the in bold and underlined, the NarI site is underlined).…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%
See 2 more Smart Citations